Sosialisasi Penggunaan Aplikasi Pemantauan Kasus Stunting di Desa Kemuning Lor Kabupaten Jember - Demiawan Rachmatta Putro Mudiono; Indah Muflihatin; Andri Permana Wicaksono (Indonesian Journal Publisher, 2023)
In 2016, around 22.9% or 154.8 million children worldwide suffered from stunting at the age of under 5 years. Stunting is defined as the length or height below the standard. Stunting is measured by a z-score of height and age of more than 2 standard deviations which is below the World Health Organization (WHO) Child Growth Standards. Based on the results of observations on November 25, 2022 in Kemuning Lor Village, the community service team found that cadres and mothers could be said to be of productive age with an average of already having smartphones which were underutilized in monitoring the nutritional status of toddlers. In community service activities, an application was developed that is useful in reducing and monitoring the number of stunting cases in Kemuning Lor Village, Jember Regency. The implementation methods carried out in this community service activity are literature (literary study), location surveys, application design and outreach. As for the results of this community service activity, 90% of posyandu cadres feel helped by the baby nutrition monitoring application. In the future this application will be integrated from each region so that stunting cases in Jember Regency can be monitored through one application.